Survei Kondisi Pengelolaan Sampah Masyarakat Desa Silungkang Duo, Kota Sawahlunto Sebagai Dasar Pelaksanaan Edukasi Pada Program Kuliah Kerja Nyata - Ikhsan Maulana; Reachel Natania Monteza; Nadhira Endiani; Sangra Pratam; Azharia Fathia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study aims to identify the condition of community waste management in Silungkang Duo Village, Sawahlunto City, as a basis for implementing educational programs in the Community Service Program (Kuliah Kerja Nyata/KKN). The method used is a survey with a descriptive quantitative and qualitative approach through observations, interviews, and questionnaires distributed to the community. The results show that waste management in the village is still not optimal, indicated by low public awareness in waste sorting, limited facilities and infrastructure, and a lack of socialization regarding proper waste management practices. Most community members still dispose of waste improperly or burn it without considering environmental impacts. Therefore, a structured and sustainable educational program is needed to improve community knowledge and awareness in waste management. The findings of this study are expected to serve as a basis for designing effective educational programs during the KKN implementation, thereby encouraging behavioral changes toward better and more environmentally friendly waste management.